IMPROVING STERILE COMPOUNDING OF PARENTERAL PREPARATIONS BY PHARMACY TECHNICIANS IN MBINGO BAPTIST HOSPITAL PHARMACY. - Brendaline, Fombe; Nalubega, Jane Frank; Akankwasa, Edith; Okello, Elizabeth; Kavuma, David; Naggulu, Immaculate Posperia (Student’s Journal of Health Research Africa, 2025)
Abstract Breaching the required standards for sterile compounding results in patient harm and death. Three deaths have been recorded in Mbingo Baptist Hospital resulting from contaminated sterile preparations compounded by the pharmacy. This is due to a lack of training, policy and procedures, a proper compounding facility and equipment, and poor aseptic techniques. To address these problems, a project was initiated and is ongoing. The goal of the project is to contribute to the improvement of the quality of compounded sterile parenteral preparations and ensure they are free from contamination and safe for inpatients in Mbingo Baptist Hospital from May 10th, 2023, to November 12th, 2024. The objectives are to improve the facility and equipment for sterile compounding by the 12th of November 2023, enhance personnel knowledge and skills by the 30th of December 2023, and institute a policy and standard operating procedures for sterile compounding by the 15th of April 2024. The project implementation strategy is through training, construction, and equipment purchase. The expected outcome of this project is six pharmacy technicians trained in sterile compounding, a separate facility and laminar air flow hood for sterile compounding, and a policy and standard operating procedures for sterile compounding. The acquired knowledge and skills will be sustained by assessing the aseptic technique skills of trained personnel every 6 months through media field and glove finger tests.